2015
DOI: 10.1093/brain/awv102
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor signalling in multiple sclerosis: inhibition of myelination and induction of pro-inflammatory environment by FGF9

Abstract: Remyelination failure plays an important role in the pathophysiology of multiple sclerosis, but the underlying cellular and molecular mechanisms remain poorly understood. We now report actively demyelinating lesions in patients with multiple sclerosis are associated with increased glial expression of fibroblast growth factor 9 (FGF9), which we demonstrate inhibits myelination and remyelination in vitro. This inhibitory activity is associated with the appearance of multi-branched 'pre-myelinating' MBP+ / PLP+ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 85 publications
8
75
0
Order By: Relevance
“…FGF9 was found in active demyelinating lesions in patients with MS, and was made responsible for tissue damage, lesion formation through activating proinflammatory cytokine and chemokine production in the CNS. In vitro FGF9 inhibited myelination and remyelination .…”
Section: Discussionmentioning
confidence: 99%
“…FGF9 was found in active demyelinating lesions in patients with MS, and was made responsible for tissue damage, lesion formation through activating proinflammatory cytokine and chemokine production in the CNS. In vitro FGF9 inhibited myelination and remyelination .…”
Section: Discussionmentioning
confidence: 99%
“…Quantification was carried out using CellProfiler Image Analysis software (Broad Institute) (Carpenter et al, 2006;Lindner et al, 2015).…”
Section: Myelination and Opc/oligodendrocyte (Ol) Quantificationmentioning
confidence: 99%
“…Fibroblast growth factor 9 (FGF9) is a 26 kDa secreted protein in the fibroblast growth factor family that is essential and sufficient for development. Mutations in Fgf9 have been reported to be associated with several human diseases, such as prostate cancer, endometriosis, and multiple sclerosis . In addition, studies have confirmed that Fgf9 is a crucial regulatory gene of the lung mesenchyme .…”
Section: Introductionmentioning
confidence: 94%